NATURAL SWIMMING POOLS: AN NBS APPLICATION FOR WATER SAVING IN ECOTOURISM CENTERS IN JALCOMULCO, VERACRUZ, MÉXICO - Arriaga, Diana Eliud Palacios; Bernal, Clementina Barrera (Seven Editora, 2025)
Ecotourism is a practice that suggests responsible travel in natural areas, improving the well-being of local populations; However, little is discussed about the water needs of the sector. It is estimated that a tourist uses 300 liters by day (Gössling et al., 2012); for optimize the use of water resources, in Jalcomulco, Veracruz; four hotels and four ecotourism centers were characterized, estimating the water consumption of the infrastructure, especially the swimming pools. Finally, a natural swimming pool was designed and built with NbS at the La Aldea Ecotourism Center located in the town; where the treatment of water quality is based on biochemical processes carried out by aquatic plants, swamps and the microorganisms associated with them. This is one of the few works on the implementation of natural pools in Veracruz, providing useful information for future research.DOI: https://doi.org/10.56238/sevened2025.036-087